Comparison of the machine learning methods to predict wildfire areas - YILDIZ, KAZIM (My University, 2022)
In the last decades, global warming has changed the temperature. It caused an increasing the wildfire in everywhere. Wildfires affect people's social lives, animal lives, and countries' economies. Therefore, new prevention and control mechanisms are required for forest fires. Artificial intelligence and neural networks(NN) have been benefited from in the management of forest fires since the 1990s. Since that time, machine learning (ML) methods have been used in environmental science in various subjects. This study aims to present a performance comparison of ML algorithms applied to predict burned area size. In this paper, different ML algorithms were used to forecast fire size based on various characteristics such as temperature, wind, humidity and precipitation, using records of 512 wildfires that took place in a national park in Northern Portugal. These algorithms are Multilayer perceptron(MLP), Linear regression, Support Vector Machine (SVM), K-Nearest Neighbors (KNN), Decision Tree and Stacking methods. All algorithms have been implemented on the WEKA environment. The results showed that the SVM method has the best predictive ability among all models according to the Mean Absolute Error (MAE) metric.

Son on yılda, küresel ısınma sıcaklığı değiştirdi. Orman yangınlarının her yerde artmasına neden oldu. Orman yangınları insanların sosyal yaşamlarını, hayvan yaşamlarını ve ülke ekonomilerini etkiler. Bu nedenle orman yangınları için yeni önleme ve kontrol mekanizmalarına ihtiyaç duyulmaktadır. 1990'lı yıllardan itibaren orman yangınlarının yönetiminde yapay zeka ve sinir ağlarından yararlanılmaktadır. O zamandan beri, çevre biliminde çeşitli konularda makine öğrenmesi (ML) yöntemleri kullanılmıştır. Bu çalışma, yanan alan boyutunu tahmin etmek için uygulanan ML algoritmalarının performans karşılaştırmasını sunmayı amaçlamaktadır. Bu yazıda, Kuzey Portekiz'deki bir milli parkta meydana gelen 512 orman yangınının kayıtları kullanılarak sıcaklık, rüzgar, nem ve yağış gibi çeşitli özelliklere dayalı olarak yangın boyutunu tahmin etmek için farklı ML algoritmaları kullanılmıştır. Bu algoritmalar Lineer regresyon, Destek Vektör Makineleri (SVM), Çok Katmanlı Algılayıcı, KEn Yakın Komşular (KNN), Karar Ağacı ve Yığınlama yöntemleridir. Tüm algoritmalar WEKA ortamında gerçeklenmiştir. Sonuçlar, Ortalama Mutlak Hata (MAE) metriğine göre tüm modeller arasında SVM yönteminin en iyi tahmin yeteneğine sahip olduğunu göstermiştir.
Keywords: Machine Learning; Random Forest; Support Vector Machine; Decision Tree; WEKA; Makine Öğrenmesi; Destek Vektör Makineleri; Karar Ağacı